Wavelength division multiplexing passive optical networks (WDM PONs) With Downstream DPSK and Upstream Remodulated OOK using Injection-Locked Fabry-Perot Laser Diodes (FP-LDs) - El-Nahal, Fady (Photonics Letters of Poland, 2015)
<!– saved from url=(0022)http://internet.e-mail –> Wavelength Division Multiplexing-Passive Optical Network (WDM-PON) system based on the injection locked Fabry-Perot laser diode (FP-LD) has been investigated. The system has been demonstrated without dispersion compensation for both 10Gbps Differential phase-shift keying (DPSK) downstream signal and 2.5Gbps On-off keying (OOK) upstream signal respectively. Error free transmission over 50-km is achieved by tailoring the parameters of the FP-LD. The BER performance of our system shows that the injection locked FP-LD is a low cost effective colourless transmitter for high-speed WDM-PONs. Full Text: PDF References E. Wong, "Next-Generation Broadband Access Networks and Technologies", J. Lightwave Technol. 30(4), 597 (2012). CrossRef F.T. An, D. Gutierrez, K.S. Kim, J.W. Lee, L.G. Kazovsky, "SUCCESS-HPON: A next-generation optical access architecture for smooth migration from TDM-PON to WDM-PON", IEEE Commun. Mag. 43(11), S40 (2005). CrossRef S.-J. Park, C.-H. Lee, K.-T. Jeong, H.-J. Park, J.-G. Ahn, K.-H. Song, "Fiber-to-the-home services based on wavelength-division-multiplexing passive optical network", J. Lightwave Technol. 22, 2582 (2004). CrossRef C.W. Chow, C.H. Yeh, "Using Downstream DPSK and Upstream Wavelength-Shifted ASK for Rayleigh Backscattering Mitigation in TDM-PON to WDM-PON Migration Scheme", IEEE Photon. J. 5(2), 7900407 (2013). CrossRef J. He, D. Yang, L. Chen, "A full-duplex radio-over-fiber system with differential phase-shift keying signals", J. Phys. Conf. 276, 012062 (2011). CrossRef L.Y. Chan, C.K. Chan, D.T.K Tong, E Tong, L.K. Chen, "Upstream traffic transmitter using injection-locked Fabry-Perot laser diode as modulator for WDM access networks", Electron. Lett. 38(I), 43 (2002). CrossRef Z. Xu, Y. J. Wen, C. J. Chae, Y. Wang, C. Lu, Proc. Opt. Fiber Commun. Conf. (OFC06), JThB72 (2006). C.H. Yeh, C.W. Chow, H.Y. Chen, J.Y. Sung, Y.L. Liu, "Demonstration of using injection-locked Fabry-Pe?rot laser diode for 10?Gbit/s 16-QAM OFDM WDM-PON", Electron. Lett. 48(15), 940 (2012). CrossRef J. H. Lee et al., "Single, Depolarized, CW Supercontinuum-Based Wavelength-Division-Multiplexed Passive Optical Network Architecture With C-Band OLT, L-Band ONU, and U-Band Monitoring", IEEE J. Light. Tech. 25(10), 2891 (2007). CrossRef Q.T. Nguyen et al., "Bidirectional Transmission in Colourless WDM-PON based on Injection-Locked Fabry-Perot Laser at 2.5 Gbit/s using Low-Cost Seeding Source", in: Proc. Eur. Conf. Opt. Commun. (ECOC), Vienna, Austria, Paper 6.5.1, (2009). DirectLink T. Yoshida, S. Kimura, H. Kimura, K. Kumozaki, T. Imai, "A new single-fiber 10-gb/s optical loopback method using phase Modulation for WDM optical access networks", J. Lightw. Technol. 24,786 (2006) CrossRef W. Hung, C.-K. Chan, L.-K. Chen, F. Tong, "An optical network unit for WDM access networks with downstream DPSK and upstream remodulated OOK data using injection-locked FP laser", IEEE Phot. Techn. Lett. 15(10), 1476 (2003). CrossRef OptiSystem Package from Optiwave.